(3GdbGehS GdeMjWs - (3GdTjQGRj GdajQhR BHGOj, CHh WGgQ, GdajQhR BHGOj, eMeO Hf jYbhH Hf eMeO Hf EHQGgje, J (B817(3g` (B1415(3es ((3jYbhH Hf ESeGYjd GdJaQjTjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg efWb GdHdZGA HGddZZj aj GdHhGOj (B... (3aUd GdgeRI, GdCHGAI cYHGAI, GdbUHI L CHGA, gPG ehVY PcQg ceG McGg GHf Lfj Yf SjHhjg dG GdeYJds
(3BNQgG (B:s
(3BNQgG(B: (3hjGA GdLRe GdeQSd GbV GdCeQ hJMPa dCf bHdgG cSQI JNdbgG hHGA GdLRe GdefHSW QCjJ YHOj (B.. (3ce JSbW dCfg dG Nda YfgGs
(3fbdJ ef fSNI efbhdI Yf fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 146s
(3cTa GdXfhf, L (B2: 1306s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GddZIs